PROSPEK PENGEMBANGAN PALA RAKYAT DI PROVINSI LAMPUNG - Lestari, Fitri Yuni; Ismono, Raden Hanung; Prasmatiwi, Fembriarti Erry (Jurnal Ilmu-Ilmu Agribisnis, 2019)
The research aimed to analyze financial feasibility and development prospect of nutmeg farming in Lampung Province.  This research was conducted in Gisting Subdistrict of Tanggamus Regency in which data was collected in September 2017 until October 2017 by survey method.  This research used primary and secondary data.  Primary data was used to answer financial feasibility analyze purpose and obtained by interview technique using questionnaires.  Secondary data in the past seven to night years was used to answer the purpose of prospect development of nutmeg farming.  The samples size of this research was 30 nutmeg farmers using simple random sampling.  The data was analyzed by financial feasibility and time series linier with ARIMA model.  The results of the study showed that the nutmeg farming was feasible, and development prospect of nutmeg farming based on production and nutmeg seeds export had a good potential for the future. Key words: ARIMA, development, financial, nutmeg, prospect